Formação e atuação em coensino dos egressos de licenciatura em educação especial - Stopa, Paula Cristina (2021)
This study problematizes the initial training of Special Education teachers and the acting model based on co-teaching or collaborative teaching. The theoretical framework adopted in this study is based on the tripod: legal frameworks of the Special Education policy in Brazil; background on the training of specialized teachers for school inclusion; and the concept of Co-teaching or Collaborative Teaching as a Model for Provision of Services provided to PAEE students, as presented in the Special Education literature. The general objective was to analyze and evaluate the Degree courses in Special Education (LEEsp), in the aspect of training for acting in Co-teaching, understanding the training experiences provided and the perspective of professionals who graduated from Degree courses in Special Education. The specific objectives were: i. Analyze training experiences in the curriculum of LEEsp courses; ii. Identify the space of professional performance, in co-teaching, of graduates in LEEsp; iii. To analyze the influence of training bases in Co-teaching on the performance of professionals who graduated from LEEsp courses; and iv. Identify and analyze the training experiences lived and how they contributed to the training of professionals who graduated from LEEsp. The design involved a descriptive research study with a qualitative focus, having as context two LEEsp courses (Federal University of Santa Maria and Federal University of São Carlos) and involved 51 Special Education teachers graduated from LEEsp courses. The study took place in the following stages: 1) Survey with 51 professors who graduated from both courses, with collections via Google Form; 2) Study on formative and acting experiences in Co-teaching, based on semi-structured interviews with 17 participants; 3) Documentary study of the political pedagogical projects of the LEEsp courses. The results involve analysis of the training experiences contained in the LEEsp course curriculum; the spaces of professional performance in co-teaching of graduates in LEEsp; the influence of training bases in Co-teaching on the performance of professionals who graduated from LEEsp courses; and how the training experiences lived contributed to the training of professionals who graduated from LEEsp. It was concluded that the curriculum has provided training for the collaborative work articulated between the Special Educator and the common Educator, demonstrating that the courses have revised the acting models of this professional, changing the vision of training the special educator to work only in extra care common class with promising results. It was observed that the initial training enabled changes in the interviewees' lives, positively impacting the construction of the professionals' identity. However, the performance in Collaborative Education still appears limited due to the extra-class specialized educational service model that has been prioritized by the national policy on Special Education since the mid 2000s.